Personality profile characteristics of patients with somatoform and anxiety-phobic disorders with phenomena of reduced criticality - M. Ye. Khomitskyi; M. Yu. Kondratenko (Zaporožskij Medicinskij Žurnal)
The aim: to study the personality characteristics and their relationship with reduced criticality manifestations by examining the personality profile of patients with somatoform and anxiety-phobic disorders.